American versus Arab/Islamic family businesses - Sonfield, Matthew C. (2014)
Purpose – The purpose of this research was to compare the use of non-family-members in the higher-level management team of Arab/Islamic family businesses versus American family businesses. Design/methodology/approach – This research gathered survey data and tested the hypothesis using analysis of covariance. Findings – American family businesses engaged the services of non-family-member managers to a statistically significant greater degree than did Arab/Islamic family businesses. Originality/value – The research literature on Arab/Islamic entrepreneurship is very limited, and a family business study of this nature has not been previously conducted. This study furthermore challenges the common assumption that the findings generated in one specific country can usually be generalized to the broader phenomenon of family business, as it exists in most countries.